The relationship between the Muslim world and the United States and the root of Islamophobia in America - Abdul Rauf, Feisal (Journal of ecumenical studies, 2016)
The problems between the United States and the Muslim world have nothing to do with American values or American business. These problems are too often oversimplified, but, if we analyze and sort them, we find that they fall into several identifiable categories: political, economic/socioeconomic, identity, theological/belief, and perception. Breaking up larger problems into constituent and identifiable parts helps us carefully to consider each problem component and craft initiatives in each of these arenas or spaces.